Exploring the Q‐markers of Angelica sinensis (Oliv.) Diels of anti‐platelet aggregation activity based on spectrum–effect relationships. (15th June 2022) - Zhang, Kaixue; Shen, Xue; Yang, Li; Chen, Qin; Wang, Ningning; Li, Yimeng; Song, Pingshun; Jiang, Min; Bai, Gang; Yang, Pingrong; Yang, Zhigang
Abstract: The radix of Angelica sinensis (Oliv.) Diels (RAS) is widely used in medicinal and dietary applications in China, and has the function for replenishing and invigorating the blood, stopping pain and moistening the intestines. In this study, RAS from the main geoherb regions showed better efficacy in inhibiting Adenosine diphosphate‐ or arachidonic acid‐induced platelet aggregation than those from non‐geoherb regions. In addition, the HPLC fingerprints of 30 batches of RAS, as part of the comprehensive evaluation of RAS, were established and used for spectral efficiency to screen the quality markers for anti‐platelet aggregation activities. Five compounds in RAS—senkyunolide I, uridine, guanine, ferulic acid and adenosine—were demonstrated to contribute significantly to the anti‐platelet aggregation activity. These bioactive compounds, especially senkyunolide I and ferulic acid with stronger activities, could be used as quality markers of RAS for quality control of RAS.